2021
DOI: 10.3390/ma14226792
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Artificial Intelligence to Predict the Superplasticizer Demand of Self-Consolidating Concrete Incorporating Pumice, Slag, and Fly Ash Powders

Abstract: Self-consolidating concrete (SCC) is a well-known type of concrete, which has been employed in different structural applications due to providing desirable properties. Different studies have been performed to obtain a sustainable mix design and enhance the fresh properties of SCC. In this study, an adaptive neuro-fuzzy inference system (ANFIS) algorithm is developed to predict the superplasticizer (SP) demand and select the most significant parameter of the fresh properties of optimum mix design. For this purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In addition, Arslan [23] compared the prediction of the torsional strength of RC beams between ANNs and different design codes for the research feasibility of ANN. In the ML modelling approaches, fuzzy logic, random forests and support vector machines have been reported in predicting concrete mechanical properties such as compressive strength and elastic modulus that are largely consistent with the simulation results of neural networks [11,24,25]. However, these methods, except neural networks, usually require a significant computational effort in finding an optimal solution to a complex problem.…”
Section: Introductionmentioning
confidence: 64%
“…In addition, Arslan [23] compared the prediction of the torsional strength of RC beams between ANNs and different design codes for the research feasibility of ANN. In the ML modelling approaches, fuzzy logic, random forests and support vector machines have been reported in predicting concrete mechanical properties such as compressive strength and elastic modulus that are largely consistent with the simulation results of neural networks [11,24,25]. However, these methods, except neural networks, usually require a significant computational effort in finding an optimal solution to a complex problem.…”
Section: Introductionmentioning
confidence: 64%
“…When FA was used, an additional amount of the superplasticizer was required compared to the reference mixture at a substitution rate of 25%; a higher slump than that of the reference mix was observed at a substitution rate of 50%. Previous studies have shown that FA tends to decrease slump when FA replaces weight because FA density is lower than that of cement, and the specific surface area of the binder increases [44,45]. When a substitution rate of 50% was used, the ball bearing effect of using FA had a greater impact.…”
Section: Slumpmentioning
confidence: 97%
“…In the PSO algorithm, particles are the building blocks of the population, and they work together to obtain the optimum approach to the target [51,62,67]. For this reason, it is called swarm intelligence.…”
Section: Particle Swarm Optimization (Pso)mentioning
confidence: 99%
“…Neural networks (NNs) are a common group of techniques that are employed to predict and analyse test results [58][59][60][61]. The development of different types of NNs has led to several algorithms including artificial neural networks (ANNs), adaptive neuro-fuzzy inference system (ANFIS) and multi-layer perceptron (MLP) [62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%